Study on macro performance and micro-analysis of high strength grouting material - Benan Shu; Guodong Zeng; Min Zhou; Yongling Li; Yanfei Ren; Tengyu Yang; Keyi Qiu (Materials Research Express, 2023)
Wind turbine duct put forward higher requirements for the performance of grouting materials. In order to obtain more economical high strength grouting materials (HSG), three kinds of low price main components, cement, quartz sand (QS) and fly ash microspheres (MS) were utilized and developed. Macro performance and micro-analysis of the HSG were conducted. The macro performance tests revealed that the mix proportion of HSG is determined as, cement: QS: MS: superplasticizer: swelling agent = 80:10:10:0.3:0.12, water binder ratio is determined as 0.26. Compressive and flexural strength of the HSG exceeding 120 MPa and 20 MPa respectively. The HSG also showed good fluidity and homogeneity. The micro-analysis showed that a complete and continuous micro-structure was formed and interface transition zone could not be observed. XRD and TG-DSC results meant that the amount of AFt increased. On the contrary, the amount of Ca(OH) _2 decreased. pore diameter of the HSG was mostly 10 nm. The addition of swelling agent and MS did not changed the types of hydration products of HSG, but the pore structure was optimized. Due to the cheap components, HSG contributed higher profits with the lower price, and which perform good economic benefits and market competitiveness.